50 years of the psychological clinic of the Universidad Nacional Mayor de San Marcos. Past and present, Tribute to his trajectory - Orellana Manrique, Oswaldo (2007)
It is made an historical evaluation of the 50 years of the psychological doctor's office of the UNMSM, having identified the periods of development in four stages, that allows to valorize the specialized work, as well as the difficulties and tendencies of institutional development.